Punctured torus groups and 2-bridge knot groups (I) - Akiyoshi Hirotaka; Sakuma Makoto; Wada Masaaki; Yamashita Yasushi (Berlin Springer-Verlag, 2007)
This monograph is Part 1 of a book project intended to give a full account of Jorgensen's theory of punctured torus Kleinian groups and its generalization, with application to knot theory.
Keywords: Kleinian groups; Knot theory; Torus (Geometry)